Phân bố dông và lốc trên lãnh thổ Việt Nam - Thông, Mai Trọng; Hiền, Nguyễn Thị; Hòa, Vũ Thị; Thủy, Hoàng Lưu Thu (Vietnam Journal of Earth Sciences, 2004)
Distribution of thunderstorm and whirlwinds on the territory of Vietnam